PharmacoEconomics - Open Healthcare Interventions and Outcomes - Wrightson, Timothy; Carswell, Christopher I.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Adis.)
Aims and Scope PharmacoEconomics - Open focuses on applied research on the economic implications and health outcomes associated with drugs, devices and other healthcare interventions. The journal includes, but is not limited to, the following research areas: Economic analysis of healthcare interventions Health outcomes research Cost-of-illness studies Quality-of-life studies Articles published in PharmacoEconomics - Open may be accompanied by plain language summaries, to assist patients, caregivers and others in understanding important medical advances All manuscripts are subject to peer review by international experts. Letters to the Editor are welcomed and will be considered for publication.
Keywords: Medicine; Pharmacy management; Medicine & Public Health; Pharmacoeconomics and Health Outcomes